Second reduced intensity conditioning allogeneic transplant as a rescue strategy for acute leukaemia patients who relapse after an initial RIC allogeneic transplantation: analysis of risk factors and treatment outcomes - Vrhovac, Radovan; Labopin, M.; Ciceri, F.; Finke, J.; Holler, E.; Tischer, J.; Lioure, B.; Gribben, J.; Kanz, L.; Blaise, D.; Dreger, Peter; Held, G.; et al. (Bone marrow transplantation, 2016)
Limited therapeutic options are available after relapse of acute leukaemia following first reduced intensity conditioning haematopoietic stem cell transplantation (RIC1). A retrospective study on European Society for Blood and Marrow Transplantation (EBMT) registry data was performed on 234 adult patients with acute leukaemia who received a second RIC transplantation (RIC2) from 2000 to 2012 as a salvage treatment for relapse following RIC1. At the time of RIC2, 167 patients (71.4%) had relapsed or refractory disease, 49 (20.9%) were in second CR and 18 (7.7%) in third or higher CR. With a median follow-up of 21 (1.5-79) months after RIC2, 51 patients are still alive. At 2 years, the cumulative incidence of non-relapse mortality (NRM), relapse incidence (RI), leukaemia-free survival (LFS) and overall survival (OS) were 22.4% (95% confidence interval (CI): 17-28.4), 63.9% (56.7-70.1), 14.6% (8.8-18.5) and 20.5% (14.9-26.1), respectively. In patients with acute myelogenous, biphenotypic and undifferentiated leukaemia (representing 89.8% of all patients), duration of remission following RIC1 >225 days, presence of CR at RIC2, patient’s Karnofsky performance status >80 at RIC2 and non-myeloablative conditioning were found to be the strongest predictors of patients’ favourable outcome.
Published online 5 October 2015
Gesehen am 04.06.2020